Numerical Analysis of Analog Signals for Data Processing in Electrocardiology - Koechlin, R. (Methods of Information in Medicine, 1965)
The principle of a new data acquisition system is given for the numerical analysis of a visualized analogue signal. The operator chooses the sequence of interest. A 1/4 inch magnetic tape loop repeats the sequence on an oscilloscope screen. With numerical knobs he can either obtain automatically the full series of coded samples within the limits of a chosen zone of interest, or pick up the point by point coordinates of the only sample or segment he expects to be pertinent. The selected samples are brightened on the screen. The data are immediately made available in printed numbers to the physician for the patient’s medical file, or on punched tape for further processing and for Telex transmission.